2021
DOI: 10.1111/conl.12829
|View full text |Cite
|
Sign up to set email alerts
|

For the sake of resilience and multifunctionality, let's diversify planted forests!

Abstract: This is an open access article under the terms of the Creative Commons Attribution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
128
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 209 publications
(180 citation statements)
references
References 26 publications
1
128
0
2
Order By: Relevance
“…As a result of these activities, many native New Zealand tree species that were once common are now classified as threatened or protected in both rural and urban areas [25,26]. However, New Zealand is currently host to a wide range of alien species, defined as species non-native to New Zealand [24][25][26][27][28][29][30]. Since the 1990s, alien (non-native) tree species have had a significantly higher afforestation rates than native species in New Zealand [31,32].…”
Section: The Decline Of Native Forests After Human Settlement In New Zealandmentioning
confidence: 99%
“…As a result of these activities, many native New Zealand tree species that were once common are now classified as threatened or protected in both rural and urban areas [25,26]. However, New Zealand is currently host to a wide range of alien species, defined as species non-native to New Zealand [24][25][26][27][28][29][30]. Since the 1990s, alien (non-native) tree species have had a significantly higher afforestation rates than native species in New Zealand [31,32].…”
Section: The Decline Of Native Forests After Human Settlement In New Zealandmentioning
confidence: 99%
“…Similarly, exotic pine plantations in New Zealand can support a diverse native flora in their understorey ( Forbes et al, 2019 ). However, as monospecific plantations typically provide less non-production-related ecosystem services on all but least degraded sites ( Bauhus et al, 2010 ), future planted forests may be designed, and management measures adapted, to integrate ineradicable alien species – maximizing multifunctionality ( Liu et al, 2018 ; Messier et al, 2021 ). In specific, Baeten et al (2019) reported that targeting high tree productivity does not necessarily trade-off against other ecosystem services.…”
Section: Can Exotic Species Maintain Ecosystem Functioning Ecosystem Services?mentioning
confidence: 99%
“…Likewise, promoting species‐rich plantations will enhance the carbon storage potential of managed forests in addition to reforestation projects. Transdisciplinary projects are needed to understand both biodiversity and production constraints and objectives 8 . Here, we suggest that biodiversity‐ecosystem functioning (BEF) research should take a sharp turn toward transdisciplinary research to better meet the practical demands of land managers, practitioners, and restoration initiatives 8 .…”
Section: Diversifying Forests To Mitigate Carbon Emissionsmentioning
confidence: 99%
“…Transdisciplinary projects are needed to understand both biodiversity and production constraints and objectives 8 . Here, we suggest that biodiversity‐ecosystem functioning (BEF) research should take a sharp turn toward transdisciplinary research to better meet the practical demands of land managers, practitioners, and restoration initiatives 8 . For instance, Mao et al 17 proposed and applied a holistic modelling framework to link biodiversity conservation and socioeconomic goals in French mountain resort areas.…”
Section: Diversifying Forests To Mitigate Carbon Emissionsmentioning
confidence: 99%